2020
DOI: 10.33448/rsd-v9i9.7979
|View full text |Cite
|
Sign up to set email alerts
|

Is the combination of corticosteroids plus NSAIDs improve the preemptive analgesia after third molars surgery? A systematic review and meta-analysis

Abstract: This study aimed to perform a systematic review and meta-analysis to evaluate the preemptive action of the combination of corticosteroids and non-steroidal anti-inflammatory drugs (NSAIDs) or both drugs singly after third molars surgery. It was performed a search on the PubMed/MEDLINE, Scopus, and Cochrane databases, according to the PRISMA criteria, with no time restrictions up to March 2020. The postoperative pain was evaluated, qualitatively, through the visual analogue scale (VAS) and the number of rescue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…6,13 There are many studies in the literature reporting that the preemptive use of NSAIDs in third molar surgery reduces pain from the postoperative 24-hour to the 7-day. 6,9,15,16 In this study, it was shown that the pre-operative use of IV dexketoprofen and Acetaminophen Intake Dose (mg) ibuprofen after third molar tooth extraction had positive contributions to analgesia in the postoperative 24-hour and reduced the amount of rescuer-analgesic intake and edema in the postoperative 24-hour.…”
Section: Discussionmentioning
confidence: 85%
“…6,13 There are many studies in the literature reporting that the preemptive use of NSAIDs in third molar surgery reduces pain from the postoperative 24-hour to the 7-day. 6,9,15,16 In this study, it was shown that the pre-operative use of IV dexketoprofen and Acetaminophen Intake Dose (mg) ibuprofen after third molar tooth extraction had positive contributions to analgesia in the postoperative 24-hour and reduced the amount of rescuer-analgesic intake and edema in the postoperative 24-hour.…”
Section: Discussionmentioning
confidence: 85%